On the sensitivity of poisson EWMA control chart - Abujiya, Mu’azu Ramat (2013)
Until recently, the application of the runs rules was restricted to the Shewhart-type control charts. In this paper, we propose an EWMA control chart with fast initial response (FIR) using ?? ??/ runs rule scheme for monitoring Poisson observations. Using Monte Carlo simulations, we studied and compared the average run length (ARL), the Average Ratio ARL (ARARL), the Average Extra Quadratic Loss (AEQL) and the Performance Comparison Index (PCI) of the proposed runs rule FIR Poisson EWMA chart with some other Poisson EWMA procedures. It is shown that the use of runs rule and FIR feature has substantially increased the sensitivity of Poisson EWMA control chart without decreasing the out-of-control ARL. The proposed chart is more effective in detecting moderate shifts in Poisson process than some of the existing procedures.